A Research of Occupational Happiness of R Primary School Teachers based on JD-R Model - Qiu, Xiaoyuan; Li, Zhongwu (International Journal of Multidisciplinary in Management and Tourism, 2022)
Tutoring activities that were previously distributed to out-of-school training institutes have been shifted to the work of in-school instructors as part of China’s “double reduction” program. As a result, teachers are under more stress than ever before, potentially affecting pupils’ education. As a result, occupational satisfaction among teachers has now been considered a critical aspect of education. The JD-R model (Job Demand-Resources) discusses the factors influencing elementary school teachers’ occupational happiness in the context of increasing job content and uneven distribution of educational resources to find effective ways to improve their occupational happiness. One hundred twenty-five staff samples were obtained from an R elementary school for the study. Result reveals that occupational, personal, organizational, and social aspects significantly affect teachers’ occupational happiness.